Seed germination and seedling development in response to submergence in tree species of the Central Amazonian floodplains - Melo, Risolandia Bezerra de; Franco, Augusto C.; Silva, Clovis Oliveira; Piedade, Maria Teresa Fernandez; Ferreira, Cristiane Silva (Aob Plants, 2015)
Successful germination and seedling establishment are crucial steps for maintenance and expansion of plant populations and recovery from perturbations. Every year the Amazon River and its tributaries overflow and flood the adjacent forest, exerting a strong selective pressure on traits related to seedling recruitment.We examined seed characteristics, stored reserves, germination, seedling development and survival under water of eight representative tree species fromthe lower portions of the flood-level gradient to identify adaptive strategies that contribute to their regeneration in this extreme ecosystem. Submerged seedlings were assessed for longevity and survival until they showed symptoms of injury. At this point, the remaining healthy seedlingswere planted in unsaturated soil tomonitor recovery after re-exposure to air over 30 days. All small (seed mass ≤0.17 g) seeds had epigeal phanerocotylar-type germination, a trait that would allow plants to acquire light and CO2 in the shortest time. Cell wall storage polysaccharide was a major component of all seeds, suggesting plant investment in structural reserves. Seven of the eight species germinated and formed healthy seedlings under water that endured submersion without any apparent injury for periods of 20-115 days, depending on the species. Seedlings of some species changed the direction of root growth and grew towards the surface of the water, whichmight have increased the uptake of oxygen to the tissues. Only one of the seven species did not survive re-exposure to air. Species able to germinate and produce seedlings under submersion, which subsequently are able to establish in aerated soils, would have more time available for terrestrial growth. This is critical for colonization of lower portions of the flood-level gradient where establishment is constrained by the short terrestrial phase that precedes the next flood. © The Authors 2015.